1997
DOI: 10.1002/pro.5560060113
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the reduced Schiff‐base intermediate complex of transaldolase B from escherichia coli: Mechanistic implications for class I aldolases

Abstract: Transaldolase catalyzes transfer of a dihydroxyacetone moiety from a ketose donor to an aldose acceptor. During catalysis, a Schiff-base intermediate between dihydroxyacetone and the €-amino group of a lysine residue at the active site of the enzyme is formed. This Schiff-base intermediate has been trapped by reduction with potassium borohydride, and the crystal structure of this complex has been determined at 2.2 a resolution. The overall structures of the complex and the native enzyme are very similar; forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 21 publications
3
76
0
1
Order By: Relevance
“…This topology was consistent with the typical core structure among the superfamily of transaldolases. 4,6,20 A homodimer of NQM1/YGR043C [ Fig. 1(B)] was observed in crystal, as well as in solution demonstrated by size exclusion chromatography.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This topology was consistent with the typical core structure among the superfamily of transaldolases. 4,6,20 A homodimer of NQM1/YGR043C [ Fig. 1(B)] was observed in crystal, as well as in solution demonstrated by size exclusion chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…NQM1/ YGR043C contained all residues that are highly conserved and invariant in the transaldolase superfamily, 4 for instance, the Lys on b4 strand of the core a/b barrel, where the reduced Schiff-base intermediate is produced. 6 Three dimensional structure comparisons revealed that both the overall structure and the core a/b barrel of NQM1/YGR043C are similar to those in other transaldo- Numbers in parentheses are for the highest resolution shell. a R merge 5 P jI i 2 I m j/ P I i , where I i is the entensity of the measured reflection and I m is the mean intensity of all symmetry-related reflections.…”
Section: Comparison With Other Transaldolasesmentioning
confidence: 92%
“…Transaldolases that have the same fold and similar active site disposition of catalytic residues as class I aldolases (16) differ by the exceptional stability of their enamine (45) due to an absence of a mechanistic pathway enabling interconversion of the enamine to the iminium. Indeed, in contrast to class I aldolase, the active site of bacterial transaldolase B has no amino acid residue capable of charge stabilization vicinal to the C3 carbon of dihydroxyacetone and the enzyme lacks a mobile C-terminal region capable of mediating ␣-proton transfer (46).…”
Section: Discussionmentioning
confidence: 99%
“…The best studied example is transaldolase B (TalB) from Escherichia coli (1). A number of structural and mechanistic studies have been published elucidating its reaction mechanism (1)(2)(3)(4)(5)(6). Similar to class I aldolases the reaction proceeds via a Schiff base intermediate.…”
Section: Transaldolase (Tal)mentioning
confidence: 99%
“…In TalB, Phe 178 cannot form an H-bond with the water molecule. Hence, the catalytically important water molecule is only coordinated by 2 residues, Glu 96 and Thr 156 (6) (Fig. 6).…”
mentioning
confidence: 99%